2012
DOI: 10.1186/1471-2415-12-15
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of changes in the anterior corneal surface after Q value guided LASIK and LASEK in high myopic astigmatism for 3 years

Abstract: BackgroundTo compare the corneal high-order aberrations (HOAs), asphericity and regularity after Q-value guided laser in situ keratomileusis (LASIK) and laser epithelial keratomileusis (LASEK) in high myopic astigmatism.MethodsIn this retrospectively comparative study, we measured the corneal HOAs, asphericity indices (Q values) and corneal regularity indices preoperatively and 36 months postoperatively in 70 eyes (35 patients) with Q-value guided surgeries. All the patients with high myopic astigmatism were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 16 publications
0
8
1
2
Order By: Relevance
“…Although patients post-photorefractive keratectomy (PRK) could potentially require little or no refractive correction to achieve best-corrected visual acuity (BCVA), halos and glare can impede the postsurgical quality of vision. 9 Therefore, it is important to minimize DQ when possible because it has been shown that the loss of prolate asphericity may be the predominant factor in any functional decrease in vision after refractive surgery. 10 Clearly, greater refractive correction requires greater corneal reshaping and therefore necessitates a greater net DQ.…”
mentioning
confidence: 99%
“…Although patients post-photorefractive keratectomy (PRK) could potentially require little or no refractive correction to achieve best-corrected visual acuity (BCVA), halos and glare can impede the postsurgical quality of vision. 9 Therefore, it is important to minimize DQ when possible because it has been shown that the loss of prolate asphericity may be the predominant factor in any functional decrease in vision after refractive surgery. 10 Clearly, greater refractive correction requires greater corneal reshaping and therefore necessitates a greater net DQ.…”
mentioning
confidence: 99%
“…Corneal asphericity, spherical aberrations, and coma have been shown to increase in long-term follow-up studies after LASIK and LASEK procedures, mainly due to the healing mechanism of the cornea. [7][8][9] Myopic and hyperopic corrections using wavefront-guided LASIK have been shown to induce changes in the Q-value and spherical aberrations in opposite directions (ie, positive and negative, respectively). These changes depend on the magnitude of the refractive correction.…”
Section: Discussionmentioning
confidence: 99%
“…The Q value, being the crucial parameter of the mathematical cornea model, is re ective of the shape of the cornea and its optical properties [4,5], which includes the aberration distribution, the spherical aberration, the refractive power, and others. Today, the corneal Q value along with its distribution properties have garnered the focus of attention of the relevant studies, besides the manner in which the optical properties are impacted in the eye [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%